2020
DOI: 10.17826/cumj.735203
|View full text |Cite
|
Sign up to set email alerts
|

Ailesel meme kanseri öyküsü olan ve olmayan kadınlarda meme kanseri tanılama davranışları

Abstract: The aim of this article was to investigate the relationship between the fear of breast cancer, perceived risk, knowledge of breast cancer, and breast cancer diagnosis behaviors in women with and without a family history of breast cancer. Materials and Methods:The study used a descriptive and cross-sectional design and was carried out through face-toface interviews between December 2019 and April 2020 with 308 women who had a family history of breast cancer and were receiving breast cancer treatment in the Onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(53 reference statements)
0
6
0
3
Order By: Relevance
“…Although BSE is easy and free to apply, the application rates in countries are low and vary by country. 5,[29][30][31] According to the results of our study, the majority of women performed BSE regularly, and age, education level, and family history of cancer affected BSE behavior. In a study similar to our study results, it was found that BSE behavior was significantly higher in women who had a family history than those who did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although BSE is easy and free to apply, the application rates in countries are low and vary by country. 5,[29][30][31] According to the results of our study, the majority of women performed BSE regularly, and age, education level, and family history of cancer affected BSE behavior. In a study similar to our study results, it was found that BSE behavior was significantly higher in women who had a family history than those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…In another similar study, it was reported that the education level of women increased the frequency of BSE and the status of doing it at the right time. 30 In another study, it was determined that lack of education and awareness were among the most common reasons for women not to perform BSE. In the same study, almost half of the women had insufficient knowledge about BSE.…”
Section: Discussionmentioning
confidence: 99%
“…İnformation points in two studies conducted on the same scale in Turkey were detected to be moderate. [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] In other studies in which women's breast cancer knowledge levels were evaluated with different scales, it was stated that their knowledge level was moderate. 34-82-83-84-85-86-87 In two studies conducted on young women in Ethiopia, the breast cancer knowledge level of women was found as low.…”
Section: Discussionmentioning
confidence: 99%
“…Power analysis was performed using the G*Power 3.1 program to calculate sample size. Considering the the Health Belief Model Scale [19], Champion Breast Cancer Fear Scale [20] and Mammography Self-E cacy Scale [21] mean scores, the required sample size was determined as 134 at 95% con dence interval, 5% margin of error, 0.63 effect size, and 95% power. A total of 150 participants (75 participants in the experimental group and 75 participants in the control group) were recruited for the study with approximately 12% (16 people) extra participants, taking a possible data loss into account.…”
Section: Sample Size and Randomizationmentioning
confidence: 99%